MicroRNA-376c Impairs Transforming Growth Factor-β and Nodal Signaling to Promote Trophoblast Cell Proliferation and Invasion - Fu, Guodong; Ye, Gang; Nadeem, Lubna; Ji, Lei; Manchanda, Tanita; Wang, Yongqing; Zhao, Yangyu; Qiao, Jie; Wang, Yan-Ling; Lye, Stephen; Yang, Burton B.; Peng, Chun (Hypertension (Dallas, Tex. 1979), 2013)
Preeclampsia is a major disorder of pregnancy and a leading cause of maternal and perinatal morbidity and mortality. MicroRNAs are small noncoding RNAs that regulate gene expression posttranscriptionally. In this study, we examined the expression of miR-376c and found that miR-376c levels were downregulated in both placental and plasma samples collected from preeclamptic patients, when compared with the normal pregnant women at the same gestational stage. Overexpression of miR-376c induced trophoblast cell proliferation, migration, and invasion in HTR8/SVneo cells and promoted placental explant outgrowth. In contrast, inhibition of endogenous miR-376c resulted in a decrease in trophoblast cell invasion and placental explant outgrowth. We identified activin receptor-like kinase 5 (ALK5), a type I receptor for transforming growth factor-β, and ALK7, a type I receptor for Nodal, as targets of miR-376c. Overexpression of miR-376c repressed transforming growth factor-β and Nodal functions, whereas overexpression of ALK5 and ALK7 reversed the effects of miR-376c. These results demonstrate that miR-376c inhibits both ALK5 and ALK7 expression to impair transforming growth factor-β/Nodal signaling, leading to increases in cell proliferation and invasion. An unbalanced Nodal/transforming growth factor-β and miR-376c expression may lead to the development of preeclampsia.